Forced migrant families' assemblages of care and social protection between solidarity and inequality - Anna Amelina; Niklaas Bause (Journal of Family Research, 2020)
The article analyses various forms of care and social protection that forced-migrant transnational families exchange despite their individual members living in different countries. It presents outcomes of a small-scale empirical study of the family practices of mobile individuals from Syria and Afghanistan who arrived in Germany during and after the "long summer of 2015". Building on social protection research and transnational care studies, the article introduces the concept of care and protection assemblages, which highlights the heterogeneity, processuality and multi-scalar quality of migrant families’ efforts to improve well-being. It includes an empirical analysis that illustrates key elements of the proposed concept and shows the significance of cross-border circulation of remittances, the selectivity in the cross-border circulation of emotions and limitations on the cross-border circulation of hands-on and practical care. These findings are framed by an analysis of solidarity organizations at the meso-level and (multiscalar) securitized asylum policies at the macro-level in the German context. The proposed conceptual framework takes into consideration migrant families’ simultaneity of solidarity and inequality experiences by locating the examination of family-making at the micro-, meso-, and macro-levels of analysis.